In Situ Studies of Fe4+ Stability in β-Li3Fe2(PO4)3 Cathodes for Li Ion Batteries. Issue 4 (16th January 2015) - Christiansen, Ane S.; Johnsen, Rune E.; Norby, Poul; Frandsen, Cathrine; Mørup, Steen; Jensen, Søren H.; Hansen, Kent K.; Holtappels, Peter
Abstract : In commercial Fe-based batteries the Fe 2+ /Fe 3+ oxidation states are used, however by also utilizing the Fe 4+ oxidation state, intercalation of up to two Li ions per Fe ion could be possible. In this study, we investigate whether Fe 4+ can be formed and stabilized in β -Li3 Fe2 (PO4 )3 . The work includes in situ synchrotron X-ray powder diffraction studies (XRPD) during charging of β -Li3 Fe2 (PO4 )3 up to 5.0 V vs. Li/Li + . A novel capillary-based micro battery cell for in situ XRPD has been designed for this. During charge, a plateau at 4.5 V was found and a small contraction in volume was observed, indicating some Li ion extraction. The volume change of the rhombohedral unit cell is anisotropic, with a decrease in the a parameter and an increase in the c parameter during the Li ion extraction. Unfortunately, no increased discharge capacity was observed and Mössbauer spectroscopy showed no evidence of Fe 4+ formation. Oxidation of the organic electrolyte is inevitable at 4.5 V but this alone cannot explain the volume change. Instead, a reversible oxygen redox process (O 2− → O − ) could possibly explain and charge compensate for the reversible extraction of lithium ions from β -Li3 Fe2 (PO4 )3 .